ASTRO APEx® and RO-ILS™ are applicable to medical malpractice in radiation oncology. (November 2016) - Zaorsky, Nicholas G; Ricco, Anthony G; Churilla, Thomas M; Horwitz, Eric M; Den, Robert B
Aim: To analyze malpractice trials in radiation oncology and assess how ASTRO APEx ® and RO-ILS™ apply to such cases.Methods: The Westlaw database was reviewed using PICOS/PRISMA methods. Fisher's exact and Mann–Whitney U tests were used to find factors associated with outcomes.Results: Of 34 cases identified, external beam was used in 26 (77%). The most common factors behind malpractice were excessive toxicity (80%) and lack of informed consent (66%). ASTRO APEx pillars and ROI-LS had applicability to all but one case. Factors favoring the defendant included statute of limitations (odds ratio: 8.1; 95% CI: 1.3–50); those favoring the plaintiff included patient death (odds ratio: 0.7; 95% CI: 0.54–0.94).Conclusion: APEx and RO-ILS are applicable to malpractice trials in radiation oncology.